Ethanol extracts of mango seeds added to the diet of pigs increases antioxidant capacity of processed pork - Araújo, Lina R. S.; Watanabe, Pedro H.; Fernandes, Danilo R.; Mello, Marcelle C. A.; Maia, Irvila R. De O.; Silva, Ênio C. Da; Owen, Robert; Nascimento, Germano a. J. Do; Trevisan, Maria T. S.; Freitas, Ednardo R. (Anais da Academia Brasileira de Ciências, 2021)
Abstract Synthetic antioxidants (e.g.butylhydroxytoluene, BHT) are routinely used for to restrict oxidative processes of meat products, but they are implicated as harmful to the health of humans. Therefore natural alternatives, such as plant antioxidants, have been sought as replacements. Plant antioxidants when added to the diet can be incorporated into meat and reduce the need for the addition of synthetic antioxidants during processing. The objective of this study was to evaluate the effects of ethanol extracts of mango seeds (EEMS) in the diet of pigs on qualitative parameters and total antioxidant capacity of mortadella produced from these animals. Thirty-two pigs with an average 60 days of age were distributed among four treatments: control=no antioxidant; BHT=200ppm BHT; EEMS200=200ppm of EEMS and EEMS400=400ppm of EEMS. At 145 days of age the animals were slaughtered and loin was removed for the preparation of mortadella, which was analyzed during 90 days of storage at 4°C. A higher content of polyphenolic compounds and, total antioxidant capacity in mortadellas processed with meat of animals which consumed the EEMS400 ration after 60 and 90 days of storage was observed. EEMS polyphenolic antioxidants incorporated into pork through the diet results in an increase of total antioxidant capacity in the processed product.